PENGARUH DISPLIN KERJA, PENGAWASAN DAN IKLIM ORGANISASI TERHADAP KINERJA PEGAWAI DINAS PERUMAHAN DAN KAWASAN PEMUKIMAN KABUPATEN BATU BARA - Kamaruddin .; Putra Nanda; Zulkarnain Lubis; Heramairanisyah .; Rubianto .; Aslamiah . (Universitas Islam Sumatera Utara, 2021)
The formulation of the problem in this study is whether work discipline, supervision, and organizational climate simultaneously have a positive and significant effect on the performance employees of the Department of Housing and Settlement Kabupaten Batu Bara. This study aims to determine the effect of work discipline, supervision and organizational climate on the performance of the employees of the Department of Housing and Settlement in Batu Bara Regency. The sample in this study were all employees of the Department of Housing and Settlement Kabupaten Batu Bara, amounting to 65 people. The data analysis technique in this research is Multiple Linear Regression. The results of this study indicate; Work discipline partially has a positive but not significant effect on employee performance; Supervision partially has a positive and significant effect on employee performance; Organizational climate partially positive and significant effect on employee performance; Work discipline, supervision and organizational climate simultaneously have a positive and significant effect on employee performance.